التوجيهات اللغوية لقراءة "عمرو بن فائد" - عشماوي، شيماء أحمد السيد (جامعة الأزهر - كلية اللغة العربية بجرجا, 2021)
يهدف هذا البحث إلى دراسة قراءة من القراءات الشاذة، وجمع ما تفرق منها في بطون الكتب لأحد القراء المنسوبة إليهم هذه القراءة، وهو أبو علي عمرو بن فائد الأسواري، وذلك من خلال هذا البحث الموسوم بـــــــ "التوجيهات النحوية والصرفية والصوتية والدلالية لقراءة عمرو بن فائد"، حيث بلغ عدد القراءات المنسوبة إليه -حسب ما توصل إليه البحث -ستا وثلاثين قراءة. وقد سار البحث وفق خطة اشتملت على التمهيد، وفيه: ترجمة عمرو بن فائد الأسواري، ونبذة عن القراءات الشاذة والاحتجاج بها، ثم أربعة مباحث، تناولت قراءة عمرو بن فائد بالتوجيه، فخصص المبحث الأول للتوجيهات النحوية، وكان من مسائلها: حذف المضاف وإبقاء عمله، وحذف الموصوف وإقامة الصفة مقامه، والمبحث الثاني للتوجيهات الصرفية، ومنها: استعمال اسم الفاعل في موضع اسم المفعول، واستعمال الصفة المشبهة (فيعل) في موضع اسم الفاعل، والمبحث الثالث للتوجيهات الصوتية، ومنها: تخفيف المشدد، وإدغام التاء في الذال، والمبحث الرابع للتوجيهات الدلالية، ومنها: قراءة (قطر آن) على أنهما كلمتان لا كلمة واحدة، وقراءة (لنحرقنه) بمعنى لنبردنه. وختم البحث بأهم ما توصل إليه من نتائج، كان منها: أن القراءة الشاذة تشارك القراءة المتواترة في صحة الاحتجاج بها في العربية، وأن عمرو بن فائد قد وافق في معظم اختياراته قراءات كثير من أعلام القراءة من الصحابة وغيرهم، كأبي بن كعب، وعبد الله بن عباس، والحسن البصري، كما انفرد بثلاثة مواضع لم يشاركه فيها أحد.
This research aims to identify rare reading, and collect what differentiated from it in the books of one of the readers attributed to this reading, which is Abu Ali Amr ibn Fa’ed Al-Aswari, through this research tagged with (Linguistic analyses for reading Amr ibn Fa’ed)where the number of the readings attributed to him were thirty six readings, and the research plan was as follows The preamble, which includes: 1. Definition of Amr ibn Fa’ed Al-Aswari 2. An overview of the rare readings and the inference of them The first topic: syntactic analyses for reading Amr ibn Fa’ed The second topic: Morphological analyses for reading Amr ibn Fa’ed The third topic: phonemic analyses for reading Amr ibn Fa’ed The fourth topic: the semantic analyses for reading Amr ibn Fa’ed The research reached a number of results, including identifying one of the Quran reciters and clarifying the readings attributed to him, and analyzing them linguistically in the chapters that address them: syntactically, such as: deleting the genitive and keeping its work, deleting the descriptive and establishing the adjective in its place. morphologically such as: using the subject noun in the place of the object noun. phonetically such as: dilution, diphthong, substitution semantically. The research also showed that rare reading participates in frequent reading in the validity of invoking it, and it is more acceptable to them than the anonymous poetic verse. In some of his choices, Amr ibn Fa’ed agreed with some of the companions, and many of Celebrities of the Qur'an, as he was unique in three places in which no one shared with him.
Keywords: القرآن الكريم -- القراءات القرآنية -- النحو العربي -- الإسوري، عمرو بن فائد